(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Nothing was more important than the question of survival, but in the later stage, all the people focused on online system, online education. The entire glob was dominated by COVID though some country did not affect. This paper made effort to see the activities of higher educational institutions in Manipur during COVID pandemic in relating to education, capacity building for economic development and student support. The economic impact of this crisis is huge and has hit every sector in a big way. The analysis was based on primary data that collected from students and teachers and interviewed with concerned faculty members of college.